Adaptive thermal comfort : how to design comfortable buildings / Susan Roaf, Fergus Nicol, Michael Humphreys. - Roaf, Susan; Nicol, Fergus, 1940-; Humphreys, Michael A. (Michael Alexander), 1936- (Routledge, 2017)
This volume provides a simple, step by step method for designing comfortable low energy buildings in any climate. Building on the academic principles, practices and fundamental research described in the first two volumes this book is written for building designers, owners, occupants, planners, architectural engineers, self-builders, renovators and educated laymen. It has been written to demystify the art and science of the performance and impacts of buildings and to explain how to, in practice, achieve adaptable, well-behaved and well-liked buildings.